Antioxidant Effect of Shallot Peel Infusion on Kidney Oxidative Stress in Diazinon-Induced Wistar Rats - Dina Helianti; Rosita Dewi; Ayu Munawaroh Aziz; Sheila Rachmania (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Diazinon is a pesticide widely used by farmers to control pests. Exposure to the low doses of diazinon can occur continuously through a polluted environment and diazinon residues in agricultural products. It has a nephrotoxic effect through oxidative stress mechanism. Flavonoid as antioxidant can significantly neutralize oxidative stress. Shallot peel is a source of flavonoids. This study was designed to determine the antioxidant effect of shallot skin infusion (SPI) on kidney oxidative stress in diazinon-induced Wistar rats by measuring the flavonoid level of SPI and kidney malondialdehyde (MDA) level. Rats were divided into normal, diazinon, and SPI groups. Diazinon was administered at dose of 40 mg/kgBW for 7 days followed by SPI at doses of 500, 1,000, and 2,000 mg/kgBW for 7 days. The flavonoid level of SPI was measured using spectrophotometry method and the kidney MDA level was measured using ELISA method. The flavonoid level of SPI was 96.8 mg QE/L. The results showed that the normal group had the lowest kidney MDA level of 2.585 mM/mL, the diazinon group had the highest level of 2.708 M/mL, while the SPI group at dose of of 500, 1,000, and 2,000 mg/kgBW had renal MDA levels of 2.642 mM/mL, 2.644 mM/mL, and 2.593 mM/mL. Nevertheless, the result of statistical analysis showed that the kidney MDA levels seven days after diazinon administration was not significantly different from the normal group so that SPI administration did not affect the kidney MDA level in diazinon-induced Wistar rats. Keyword: Shallot Peel, Diazinon, Oxidative Stress, Kidney Malondialdehyde